New born care in rural area: a cross-sectional study - Patil, Pushpa S.; Dixit, Umesh R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Though under five mortality and infant mortality rates are declining globally, the neonatal mortality rate has relatively remained unchanged. Poverty, illiteracy and health care services are interlinked. They play a role in neonatal mortality. The measures required to reduce for neonatal mortality are simple. The knowledge gap is the main reason why even the simplest of measures are not efficiently utilized. The objectives of the study were to study the knowledge regarding some of the cost-effective interventions influencing the health of the neonate and to examine the association between selected socio-demographic, antenatal and delivery care factors. Methods:A cross-sectional study was done in rural field practice area. Data was recorded on pre-designed and pre-tested questionnaire. Total of 84 women were interviewed to establish baseline levels of awareness regarding selected new born care factors. Statistical analysis was done using chi-square test. Results: 97.61% were given health education. 67.85% of the study subjects had no knowledge regarding cord care though 96.42% had knowledge regarding thermal care. 98.80% were aware of taking iron and folic acid tablets. 88.095% had hospital delivery. 75% of the literates said that more than 3 antenatal checkups have to be received.The association between educational status of the mothers and the knowledge regarding cord care was statistically significant at p<0.01. Conclusions:Improving new born survival is a major priority in child health today. We suggest importance of establishing good health education along with home based new born care.